THE RESEARCH OF BUSHING STRENGTHENING PROCESS ON SHORT EDGE-MARGIN HOLE - CAO ZengQiang; HU ZhaoYang; GAN XueDong; ZHAO Yong; WANG Jie; HAN ChaoZhong (Jixie qiangdu)
Strengthening problem of short-edge hole of titanium lug is an important task during a new aircraft development stage,Force Mate steel bushing process has been carried out to study the fatigue life of short-edge hole. Research the interference of 0. 5% 、1. 0% 、1. 5% 、2. 0% 、2. 5% how to effect the stress and strain around the hole with FEA,and comparisons with shortedge hole and normal hole are made as well. Then apply a cycle load on the lug to predict the fatigue life and provide a theoretical guidance for the optimum technology parameter.